2006
DOI: 10.1155/asp/2006/89013
|View full text |Cite
|
Sign up to set email alerts
|

A Content-Adaptive Analysis and Representation Framework for Audio Event Discovery from "Unscripted" Multimedia

Abstract: We propose a content-adaptive analysis and representation framework to discover events using audio features from "unscripted" multimedia such as sports and surveillance for summarization. The proposed analysis framework performs an inlier/outlier-based temporal segmentation of the content. It is motivated by the observation that "interesting" events in unscripted multimedia occur sparsely in a background of usual or "uninteresting" events. We treat the sequence of low/mid-level features extracted from the audi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
16
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…On the other hand, systems that do not rely on recognition of pre-defined context-specific cues usually require computationally expensive re-training, as e.g. in [28], where adaptation to different types of sport events (soccer, golf, etc.) is performed via audio segmentation and outlier detection in the data of each context.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, systems that do not rely on recognition of pre-defined context-specific cues usually require computationally expensive re-training, as e.g. in [28], where adaptation to different types of sport events (soccer, golf, etc.) is performed via audio segmentation and outlier detection in the data of each context.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a bipartite graph-based audiovisual alignment algorithm was introduced. In [18], a content-adaptive analysis and representation framework using graph-based approaches was proposed for audio event discovery. In that contribution, foreground cut criterion [16] was adapted to detect the foreground when the background is structured.…”
mentioning
confidence: 99%
“…Towards that end, in our previous work, we had detected audio "backgrounds" and "foregrounds" from a time series of cepstral features extracted from stored content [5]. Recall our definition of "background" and "foreground" in time series.…”
Section: Introductionmentioning
confidence: 99%
“…We have shown that one can detect highlight segments in sports audio and suspicious events in surveillance audio by detecting such "backgrounds" and "foregrounds". However, the computational complexity and the latency of the proposed approach in [5] is high.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation